2012
DOI: 10.3168/jds.2012-5775
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for fertility of dairy heifers and cows at different parities and relationships with production traits in first lactation

Abstract: The objectives of this study were to estimate genetic parameters for fertility of Brown Swiss cattle, considering reproductive measures in different parities as different traits, and to estimate relationships between production traits of first lactation and fertility of heifers and first-parity and second-parity cows. Reproductive indicators were interval from parturition to first service, interval from first service to conception, interval from parturition to conception, number of inseminations to conception,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
45
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 33 publications
17
45
6
Order By: Relevance
“…This reduces the scope for selection for female fertility in the second parity cows. In contrast, Raheja et al (1989) and Tiezzi et al (2012) detected a smaller reduction in heritabilities of fertility traits for second parity cows than reported in the present paper.…”
Section: Heritabilitycontrasting
confidence: 56%
See 1 more Smart Citation
“…This reduces the scope for selection for female fertility in the second parity cows. In contrast, Raheja et al (1989) and Tiezzi et al (2012) detected a smaller reduction in heritabilities of fertility traits for second parity cows than reported in the present paper.…”
Section: Heritabilitycontrasting
confidence: 56%
“…These results indicate that none of the evaluated fertility traits can be considered to be biologically the same trait in the first vs. second lactation. Tiezzi et al (2012) reported very high genetic correlations (> 0.92) between all the interval fertility traits in the subsequent lactation, whereas Raheja et al (1989) found very low genetic relationship between fertility in the first and second lactations. All of the herd-year and residual effects correlations of longevity with fertility traits in the first and second lactation were low (< 0.08; data not shown).…”
Section: Correlations Between Traits In the First And Second Lactationmentioning
confidence: 99%
“…Nevertheless, it is still the most important breed across all the dairy systems. In this context, the future trend of Brown Swiss will likely depend more on the maintenance or improvement of its fertility and longevity (Tiezzi et al, 2012), milkability (Povinelli et al, 2003), milk quality Macciotta et al, 2012), and harsh environment adaptation (Bovolenta et al, 2009), than on further improvements of milk productivity. The expansion of Simmental has interested almost exclusively the traditional systems, and is probably a result of an improvement of milk productivity, mainly with German and Austrian Fleckvieh and with French Montbeliarde semen, which has not affected the original dual-purpose characteristics.…”
Section: Farm Animal Biodiversitymentioning
confidence: 99%
“…The original data set was obtained from the Breeders Association of Bolzano-Bozen Province (northeast Italy) and consisted of 206,478 single inseminations performed on Brown Swiss heifers and cows from 1999 to 2008. A comprehensive description of the data set has been previously reported by Tiezzi et al (2011Tiezzi et al ( , 2012. Inseminations were validated as successful for CS when gestation length was 288 ± 15 d (mean value for Brown Swiss from Norman et al, 2009).…”
Section: Short Communicationmentioning
confidence: 99%